(3GdCbQGHGPjfs - (3GHf GdJdejP , gHI Gddg Hf UGYO Hf gHI Gddg Hf EHQGgje Hf Ydj, CHh GdMSf Gejf GdOhdI,J (B560 (3g` s ((3ceGd GdOjf Hf XgjQ GdOjf Hf GNJjGQ GdOjf eMeO GdeJWHH s)
(3ChdgG (B:s
(3CbQGHPjf efJRY ef YOI GbQGHPjfGJ eeG CNJGQI GdTjN GdCLd GdYGde GdaGVd GdChMO GdCced Cejf ehab Gdedc CHh GdMSf UGYO Hf gHI Gddg Hf EHQGgje GdeYQha HGHf GdJdejP s
(3BNQgG (B:s
(3hhQb Gdche hGdBS hGdceKQi hGdJaGM , fGaY HEPf Gddg YR hLd Je GdCbQGHPjf s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B72 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B138s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B23 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs